Effect and safety of traditional Chinese exercises for patients with type 2 diabetes: A protocol for systematic review and network meta-analysis. Issue 51 (23rd December 2021) - Zou, Lijuan; Lei, Linfeng; Kong, Chuifeng; Yu, Peiying; Li, Jiazhou; Pan, Hua-shan
Abstract: Background: Traditional Chinese exercises are more and more popular for type 2 diabetes patients for the treatment and rehabilitation; however, the comparative effectiveness and safety remains unclear. Our study aims to compare the pros and cons of these exercise interventions for type 2 diabetes by implementing a network meta-analysis. Methods: Eight databases will be searched for relevant systematic reviews including SinoMed, VIP, CNKI, Wanfang, PubMed, Embase, Web of Science and the Cochrane Library from inception to Oct 2021. Randomized controlled trials that meeting eligibility in published systematic reviews will be identified. Randomized controlled trial related to Traditional Chinese Exercises or Qigong therapy in the treatment of type 2 diabetes will be included. Two researchers conducted literature screening, data extraction and risk of bias assessment independently. Network meta-analysis of the data was performed by Stata 14.0. The Grades of Recommendations Assessment, Development and Evaluation system will be used to evaluate the rank of evidence. Results: The findings will be reported according to the preferred reporting items for systematic reviews and meta-analyses- network meta-analysis statement. This systematic review and network meta-analysis will summarize the direct and indirect evidence for different kinds of traditional Chinese exercises therapies and to rank these interventions. The results will be submitted to a peer-reviewed journal once completed. Conclusion: The network meta-analysis was designed to update and expand on previous research results of clinical trials to better evaluate the effectiveness and safety of different interventions of traditional Chinese exercises for type 2 diabetes patients. OSF Registration DOI: 10.17605/OSF.IO/MNJD6.